Konflik Watak Dan Perwatakan Dalam Saladin The Animated Series: Analisis Intertekstualiti - Hj. Md Idris, Izra Inna; Rahamad, Mohamad Saleeh; Md Syed, Md Azalan (Idealogy Journal, 2020)
This study focuses on the characters and characterization between hypo text biographical of Sultan Salahuddin al-Ayubi from the text entitled Saladin or What Befell Sultan Yusuf by Baha ed-Din or Ibnu Shaddad and hypertext Saladin the Animated Series (2010) directed by Steve Bristow. One important element in a story is characters and characterization as it developed a story. The characters and characterization were evaluated with intertextuality theory to identify the existence of text in text or in this context of study, biographical in animated series or it is also known as dialogue in a text by Julia Kristeva. The textual analysis on characters and characterization were focusing on character of Saladin, Tarik, Anisa, Duncan, and Omar. The researcher assessed the process of transformation, existence, haplology, and demitification in making a comparison. The findings showed that the director of Saladin the Animated Series, Steve Bristow, had changed the biography of Sultan Salahuddin al-Ayubi.   Keywords: Intertextuality, Animated Series, Transformation, Existence, Haplology, Demitification.   ABSTRAK Kajian ini menumpukan pemerhatian terhadap watak dan perwatakan antara hipoteks biografi Sultan Salahuddin al-Ayubi daripada teks Saladin or What befell Sultan Yusuf oleh Baha ed-Din atau Ibnu Shaddad dan hiperteks Saladin the Animated Series (2010) yang diarahkan oleh Steve Bristow. Antara elemen penting dalam sesebuah cerita ialah watak dan perwatakan kerana ia menggerakkan sesebuah cerita. Watak dan perwatakan ini dinilai dengan teori intertekstualiti untuk melihat proses teks dalam sebuah teks atau dalam konteks kajian ini, biografi dalam siri animasi atau boleh juga dikenali sebagai dialog antara teks yang dipelopori oleh Julia Kristeva. Kajian tekstual analisis watak dan perwatakan memfokuskan watak Saladin, Tarik, Anisa, Duncan, dan Omar. Pengkaji menilai proses transformasi, eksistensi, haplologi, dan demitefikasi dalam melakukan perbandingan watak dan perwatakan. Penemuan menunjukkan bahawa Pengarah Saladin the Animated Series, Steve Bristow, telah mengubah biografi Sultan Salahuddin al-Ayubi. Kata kunci: Intertekstualiti, Siri Animasi, Transformasi, Eksistensi, Haplologi, Demitefikasi.